Implementasi Permenkes Nomor 10 Tahun 2021 Tentang Pelaksanaan Vaksinasi Dalam Rangka Penanggulangan Covid-19 di Puskesmas Gayungan Surabaya - Ismarda Abdianti; Indah Murti; Dida Rahmadanik (CV Putra Publisher, 2023)
The purpose of this research is to detail how the Minister of Health's Regulation No. 10 of 2021 about the Implementation of Vaccination in the Context of Covid-19 would be carried out Mitigation at the Puskesmas Gayungan Surabaya, using content of policy indicators and context of implementation indicators (implementation environment). The research method used is a qualitative approach research method and data collection techniques used are interviews, documentation, and observation. The study's findings allow for the conclusion that the Covid-19 immunization strategy at the Gayungan Health Center is going quite well even though it is not fully maximized because there are still obstacles, namely people who have congenital diseases and people who are reluctant to get vaccines because they think that there is still no need to show proof of a vaccine. With the implementation of the Covid-19 vaccination at the Puskesmas Gayungan Surabaya, the output produced after the policy was the impact that the community was enthusiastic enough to vaccinate because of the strategy of giving rewards by the Puskesmas to attract public interest to want to be vaccinated. As well as the changes or outcomes that are obtained with this vaccination policy, the Covid death rate has also decreased. The implementation of vaccination at Puskesmas Gayungan Surabaya can run well and is also encouraged by the role of good collaboration between the public and commercial sectors, as well as sufficient resources.